Can a Shorter Workweek Induce Higher Employment? : Mandatory Reductions in the Workweek and Employment Subsidies - Erbas, S.; Sayers, Chera (Washington, D.C. : International Monetary Fund, 1999)
A reduction in the legal workweek may induce a degree of downward wage flexibility, while an employment subsidy to firms accommodates downward wage rigidity. It may be possible, therefore, to increase employment with a policy that combines a reduction in the workweek with an employment subsidy. In general, however, the long-run employment outcome is ambiguous, and a decline in output cannot be ruled out. More direct policy measures whose impact can be assessed with greater certainty-in particular, removing structural rigidities in the labor market-should be given priority to decrease long term unemployment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet